TRAINING ON ISLAMIC FUNERAL MANAGEMENT (RUKTI JENAZAH) FOR THE GENERAL PUBLIC - Mahila, Niufti Ayu Dewi; Utami, Handayani Dwi; Siswosaputro, Andy Yok; Kurniati, Marfi (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Death is a certainty in human life, and in Islamic teachings, the handling of the deceased is part of fardhu kifayah that must be carried out by Muslims. The process of rukti jenazah, which includes bathing, shrouding, performing the funeral prayer, and burial, has specific regulations in accordance with Islamic law. However, the reality in society shows that there are still many shortcomings in both knowledge and practical skills related to the implementation of rukti jenazah. This condition often leads to practices being carried out traditionally without a strong scientific foundation, as well as limited regeneration of funeral care cadres within the community. To address this challenge, the Department of Forensic Medicine, Ethics, and Medical Law, Faculty of Medicine, Universitas Islam Indonesia, organized a community service program in the form of training on rukti jenazah according to Islamic law. This activity was conducted on August 2, 2025, at the Faculty of Medicine Auditorium with a total of 45 participants from the general public. The method included lectures delivered by an expert speaker and hands-on practice using a mannequin, accompanied by facilitators in small groups. Evaluation was carried out through pre-test and post-test to measure the improvement in participants’ knowledge. The evaluation results showed a significant improvement, with the average pre-test score of 68.5 increasing to 92.5 in the post-test. All participants completed the training and received certificates as proof of their basic competence in rukti jenazah. This program successfully enhanced participants’ theoretical understanding and practical skills, and is expected to produce community cadres capable of carrying out rukti jenazah in accordance with Islamic law. Furthermore, this activity strengthens the role of academics in community service based on Islamic and humanitarian values. Keywords: Community service; fardhu kifayah; Islamic law; practical skills; rukti jenazah; training.